An integrated framework for assessing service efficiency and stability of rail transit systems. (June 2017) - Lai, Yung-Cheng; Ip, Chi-Sang
Highlights: An integrated framework to assess rail transit service efficiency and stability. New rail transit capacity model to compute degraded capacity during interruptions. A reliability module to incorporate historical data to service stability evaluation. A process to pinpoint the critical sections and time slots with high instability. A tool to rapidly assess the impact from operational changes or investment strategies. Abstract: A well-designed service plan efficiently utilizes its infrastructure and ensures an acceptable level of service stability with consideration of potential incidents that disturb or disrupt the rail transit services. To perform service evaluation, an integrated process combining capacity, resource usage, and system reliability is required to quantify service efficiency and stability in a consistent way. This study adopts capacity-based indices, "capacity utilization" and "expected recovery time", as the attributes for service efficiency and stability, and develops a comprehensive evaluation framework with three corresponding modules to incorporate capacity, service plan, and system reliability and maintainability simultaneously. The capacity analysis module computes the rail transit capacities under normal and degraded operations. The reliability module classifies and fits the proper reliability and maintainability distributions to the historical interruption data. The service efficiency and stability module analyzes the results of the previous two modules and evaluates the service efficiency and stability of rail transit service plans. Empirical results show that the established evaluation framework can not only evaluate the service efficiency and stability but also identify critical sections and time slots. This tool can help rail transit operators rapidly assess their operational changes and investment strategies related to efficiency and stability so as to provide efficient and stable services to their customers.